The piano tuner : a novel - Guo, Qiangsheng, 1964- (Arcade Publishing, 2023)
"A widower grieving for his young wife. A piano tuner concealing a lifetime of secrets. An out-of-tune Steinway piano. A journey of self-discovery across time and continents, from a dark apartment in Taipei's red-light district to snow-clad New York. At the heart of the story is the nameless narrator, the piano tuner. In his forties, he is balding and ugly, a loser by any standard. But he was once a musical prodigy. What betrayal and what heartbreak made him walk away from greatness?"--